Analisis Pengaruh Technology Acceptance Model (TAM) Dan Perceived Enjoyment Terhadap Kepuasan Konsumen Pengguna M-Business - Sugianto S; Vivi S (Universitas Muhammadiyah Pontianak, 2014)
The use of Internet technology as a medium for marketing purpose in order to obtain correspondence between marketers and consumers so that consumers can feel the perceived usefulness, perceived ease of use and perceived enjoyment in shopping satisfaction and marketers get the implication that repeat purchases by consumers. This research is explanatory research using sampling techniques that accidental sampling method combined with snowball sampling method. The data was collected through questionnaires and interviews. This study used a multiple regression analysis. The conclusion that can be derived from the results of the analysis are from three independent variables studied, only two (2) independent variables that significantly affect the variable satisfaction (satisfaction) consumer m-business users in the city of Pontianak is the variable perceived ease of use, and perceived enjoyment, while the variable perceived usefulness does not significantly affect the variable satisfaction (satisfaction) m-business consumer users in the city of Pontianak.